Fixed drug eruption due to paracetamol - Kushwah, Anjali; Kothari, Saroj; Saraswat, P. K. (International Journal of Basic & Clinical Pharmacology, 2017)
Fixed drug eruption is a common type of drug eruption seen in dermatology OPD’s. Usually it is seen with sulphonamides, salicylates, tetracyclines, oxyphenbutazones, dapsone, barbiturates, phenolphthalein, morphine, codeine, quinine, phenacetin, erythromycin, griseofulvin, mebendazole etc. We hereby report a case of fixed drug eruption due to single dose of oral paracetamol in an otherwise healthy male after one hour of consuming it. A provisional diagnosis of Paracetamol induced fixed drug eruption was made. Paracetamol was stopped and patient advised never to take Paracetamol in future. Patient was managed with prednisolone 10mg /day, cetirizine 10 mg/day, and amoxicillin 500 mg twice a day and mometasone + fusidic acid cream to be applied over the lesions.